THE CONCEPT OF LITERARY LANGUAGE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the concept of literary language, its historical development and key features. It analyzes the main stages of the formation of the literary language, starting from the Old Russian period and ending with modern trends. The views of linguists and writers on the role of the literary language in culture and society are considered.